Institutional support for continuous professional development of academics: issues and challenges - Tumar, Annyza; Asimiran, Soaib; Lope Pihie, Zaidatol Akmaliah; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
In order to remain competitive, private higher education institutions in Malaysia need to produce graduates who are employable and can contribute to the development of the nation. One of the key factors that would enable this is by supporting continuous professional development (CPD) of their academics so that the academics could enhance the quality of their teaching. This case study, using the qualitative approach, explored the perspectives of both academics and the administration of a Malaysian private higher education institution on the institutional support given. It drew data from teaching observations, interviews with both academics and university administration as well as analysis of relevant documents. Findings indicated that the academics had specific and varying needs for CPD in order to enhance the quality of their teaching. Both academics and university administration concurred that the institution provided support for CPD. It was found that there were CPD areas in which support was particularly strong and other areas which were under or had yet to be supported. There was also a recognition that as a growing institution and a new university that was evolving, a review and revision of relevant institutional policies was needed to enable stronger support in the area while remaining in line with other institutional needs.